(untitled) (Fiep Bulletin - online, 2013)
This study aims to examine the issue of directiveness in the proposal of Open Conceptions in the Physical Education teaching. Based on the concept of directiveness of Georges Snyders, it is possible to say that the proposal of Physical Education is non-directive, and consequently, more reactionary than progressist. It is urgent to think about how to work the Physical Education contents in a perspective that, in addition to the plan of the experiences of elements of corporal culture, also emphasizes the plan of the historical analysis of these elements.